MODEL LINEAR GOAL PROGRAMMING UNTUK MENENTUKAN KAPASITAS TRAFIK BTS PADA SISTEM TELEKOMUNIKASI SELULER GSM - Nafisa As Sofia; Wuryatmo Ahmad Sidik; Niken Larasati (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2014)
A BTS (Base Transceiver Station) is an element that has an important role as a receiver and transmitter of signals. A call request from a mobile phone to another through a BTS will be connected if there is a channel available. In the situation of overload, it is necessary to optimize the use of the bandwidth. This research consider the problem of optimizing the use of BTS’s bandwidth by users at four regions of Surabaya. The problem is represented as a mathematical model of the preemptive linear goal programming. The model has two optimization goals with the priority level. The method of sequential goal programming is used. Based on the solution, BTS traffic capacity can accommodate all the traffic demand from cellular phone users if the region A has 131,58 Erlang, region B has 1.425,45 Erlang, region C has 351,4 Erlang, and region D has 619,57 Erlang. The total capacity of traffic does not exceed the total capacity of BTS, because the total traffic capacity is decrease by 81,67 Erlang. The study also shows that a changing in the order of objective goal is not recommended.